Altered long noncoding RNA expression profiles in the myocardium of rats with ischemic heart failure. Issue 7 (July 2015) - Gao, Wei; Wang, Ze-Mu; Zhu, Meng; Lian, Xiao-Qing; Zhao, Huan; Zhao, Di; Yang, Zhi-Jian; Lu, Xiang; Wang, Lian-Sheng
Abstract : Aims: Despite significant advances in the treatment of coronary artery disease, the prevalence of ischemic heart failure is still increasing rapidly. Long noncoding RNAs are a novel class of gene regulators and may contribute to disease cause. The aim of the present study was to investigate the expression profiles of long noncoding RNAs and their potential functional roles in ischemic heart failure. Methods: We applied a well-established ischemic heart failure rat model and performed long noncoding RNA microarray experiments on the left ventricular tissue of rats with ischemic heart failure and under sham control. Differentially expressed long noncoding RNAs and mRNAs were identified through fold-change filtering. Bioinformatic analyses were performed to predict the potential biological roles of key long noncoding RNAs. Results: We found that 1197 long noncoding RNAs and 2066 mRNAs were upregulated, whereas 1403 long noncoding RNAs and 2871 mRNAs were downregulated in failing hearts (fold-change > 2.0). We also identified 331 pairs of differentially expressed long noncoding RNAs and nearby coding genes, which contained 291 long noncoding RNAs and 296 mRNAs. Expression levels of four long noncoding RNA–mRNA pairs, which might be involved in the pathogenesis of ischemic heart failure were confirmed by quantitative real-time PCR. Conclusion: Our study identified a set of long noncoding RNAs that were aberrantly expressed in rats with ischemic heart failure and might be involved in the pathogenesis of ischemic heart failure. The results of our study may provide a novel perspective for better understanding the molecular basis of ischemic heart failure. Abstract : Supplemental Digital Content is available in the text